Multicast routing with delay constrain based on improved CSA - ZHANG Jing; WANG Lian-hong (Tongxin xuebao)
With the application of the good gene information in the immaturity subpopulation,the improved clonal selection algorithm which was proposed,combined the principle of minimum cost and delay constrains to modify each individual gene so as to improve population.Meanwhile,an additional memory cell of the best individual accumulated in the process was set up to avoid population devolution.The optimized solution could be promptly searched and reached without prepared routing set.Simulation tests of multicast routing with delay constrain demonstrate that the improved clonal selection algorithm has better search efficiency,higher convergence speed,lower complexity of calculation,and better robust performance than the usual clonal selection algorithm and the genetic algorithm.